“The role of modern communication technology in developing the performance of television channels” - Mustafa Abbas Muhamed Ridha, Lec. Dr. (lark, 2023)
The aim of the research is to identify the most prominent technological developments that have contributed effectively to the development of the performance of television channels in terms of the quality of production related to audiovisual materials, as well as the level of workers by developing their communication skills and the inevitable keeping up with modern digital technology. Those who work in various fields in the TV channels, as the basic procedures of the research were tested on the extent of the use and employment of modern communication technology in these channels and how they developed their performance.    To achieve the objectives of the research, the researcher prepared a questionnaire that included multiple paragraphs that were presented to the respondents, according to the variation in the demographic characteristics represented by (gender, years of experience, scientific level, scientific specialization), as well as examining the contributions of modern communication technology in the development of the subject. The production and performance of television institutions, represented in the fields of (technological equipment available in television channels, the suitability of technology with the nature of television work).The stability of the tool that was employed was confirmed using the (Alpha Cronbach) coefficient, as the total stability coefficient of the tool was (0.95). In television content, the researcher also made a number of recommendations that would improve and keep pace with the most prominent digital technological innovations.
Keywords: digital technology, communication, performance development, television channels, television.